Incisal Interference Correction after Severe Extrusive Luxation Trauma during Orthodontic Treatment - M. Aarts; C. M. Suttorp (Case Reports in Dentistry)
This case report presents the treatment of a 12-year-old boy who suffered serious dental trauma, accompanied with buccal alveolar socket wall fractures, during orthodontic treatment. The maxillary right lateral incisor and canine were severely extruded and laterally luxated to the palatal side, resulting in an anterior crossbite and creating an incisal interference that prevented the jaws from closing in normal occlusion. During emergency treatment, the dentist attempted manual repositioning, but both severely extruded teeth were found to be immobile. One day after trauma, orthodontic repositioning was started using full fixed appliances with light 0.012″ nickel–titanium round wires, and this occlusal interference was corrected within 3 weeks. In the various internationally recognized treatment guidelines, the options for orthodontic repositioning for dental luxation trauma are only marginally described. Internationally accepted dental treatment guidelines may include immediate orthodontic repositioning after trauma as a treatment option in the management of dental extrusive and lateral luxation trauma.